Acid-Sensing Ion Channel 1/Calpain1 Activation Impedes Macrophage ATP-Binding Cassette Protein A1-Mediated Cholesterol Efflux Induced by Extracellular Acidification - Wang, Yuan-Mei; Tan, Mo-Ye; Zhang, Rong-Jie; Qiu, Ming-Yue; Fu, You-Sheng; Xie, Xue-Jiao; Gu, Hong-Feng (Frontiers in Physiology, 2022)
Background Extracellular acidification is a common feature of atherosclerotic lesions, and such an acidic microenvironment impedes ATP-binding cassette transporter A1 (ABCA1)-mediated cholesterol efflux and promotes atherogenesis. However, the underlying mechanism is still unclear. Acid-sensing ion channel 1 (ASIC1) is a critical H+ receptor, which is responsible for the perception and transduction of extracellular acidification signals. Aim In this study, we explored whether or how ASIC1 influences extracellular acidification-induced ABCA1-mediated cholesterol efflux from macrophage-derived foam cells. Methods RAW 264.7 macrophages were cultured in an acidic medium (pH 6.5) to generate foam cells. Then the intracellular lipid deposition, cholesterol efflux, and ASIC1/calpain1/ABCA1 expressions were evaluated. Results We showed that extracellular acidification enhanced ASIC1 expression and translocation, promoted calpain1 expression and lipid accumulation, and decreased ABCA1 protein expression as well as ABCA1-mediated cholesterol efflux. Of note, inhibiting ASIC1 activation with amiloride or Psalmotoxin 1 (PcTx-1) not only lowered calpain1 protein level and lipid accumulation but also enhanced ABCA1 protein levels and ABCA1-mediated cholesterol efflux of macrophages under extracellular acidification conditions. Furthermore, similar results were observed in macrophages treated with calpain1 inhibitor PD150606. Conclusion Extracellular acidification declines cholesterol efflux via activating ASIC1 to promote calpain1-mediated ABCA1 degradation. Thus, ASIC1 may be a novel therapeutic target for atherosclerosis.